FREE RADICAL SCAVENGING AND NOS ACTIVATION PROPERTIES OF WATER SOLUBLE CRUDE POLYSACCHARIDE FROM PLEUROTUS OSTREATUS - MITRA, PAYEL; KHATUA, SOMANJANA; ACHARYA, KRISHNENDU (Asian Journal of Pharmaceutical and Clinical Research, 2013)
The aim of this study was to investigate the antioxidant activity using different in vitro assays and nitric oxide synthase activation property of crude water soluble polysaccharide from P. ostreatus. The polysaccharide was isolated by hot water extraction and physico-chemical investigation revealed that it contained high amount of carbohydrate (mostly Î²-glucan) and low amount of protein and phenolic compounds. EC50 values for scavenging of hydroxyl radical and superoxide radical as well as chelating ability of ferrous ion were 665, 390 and 370 Âµg/ml respectively. The polysaccharide also showed potential nitric oxide synthase activation properties. This mushroom might be a good source of bioactive compounds.